Developing Critical Thinking Through Islamic Education: A Systematic Review of Contemporary Approaches - Huzaiman Hushin; Yousif Mahmadov; Markhabat Bolat; Mohammad Ahmad Bani Amer (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2025)
This study aims to examine contemporary approaches to developing critical thinking through Islamic education by systematically reviewing recent scholarly literature. The research employs a qualitative library research design using a systematic literature review methodology. Data were collected from peer-reviewed journal articles, academic books, conference proceedings, policy reports, and educational studies. The selected literature was analyzed using thematic content analysis to identify major theoretical foundations, pedagogical approaches, challenges, and emerging trends related to critical thinking development in Islamic educational contexts. The findings reveal that Islamic education possesses substantial intellectual resources for fostering critical thinking through concepts such as ta‘aqqul (reasoning), tafakkur (reflection), ijtihad (independent reasoning), and ‘ilm (knowledge). Contemporary approaches including inquiry-based learning, reflective learning, problem-based learning, collaborative learning, dialogical pedagogy, ethical reasoning, and digital literacy have demonstrated significant potential for enhancing higher-order thinking skills. The study further finds that effective critical thinking development requires integrated efforts involving curriculum reform, teacher professional development, assessment innovation, and responsible use of educational technologies. The novelty of the study lies in the development of the Islamic Critical Thinking Development Framework (ICTDF), which synthesizes Islamic educational philosophy, critical thinking theory, constructivist learning, ethical reasoning, and digital literacy into a comprehensive conceptual model. The study concludes that Islamic education can play a significant role in cultivating intellectually capable, ethically responsible, and critically engaged learners in the twenty-first century